Severe gastroparesia associated with the use of GLP-1 receptor agonists for weight loss - Chávez-Sánchez, Siomara Aransuzú (2024)
Initially developed as medications for diabetes mellitus, GLP-1 agonists have popularity in the treatment of obesity and weight loss. The present case describes a 69-yearold woman with a history of peptic ulcer and use of NSAIDs, pain and oral intolerance refractory to conventional management, for which an digestive endoscopy was performed, diagnosing severe gastroparesis. Asking the story, revealed surreptitious use of semaglutide. She continued with and the symptoms resolved spontaneously. The present case report potential risks of the use of GLP-1 analogues in the context of endoscopy with sedation.